Absorption of short-wave radiation in the atmosphere over India in winter - AGNIHOTRI, CL; SINGH, MS (MAUSAM, 1987)
Considering the importance of radiation studies for the World Climate Programme (WCP) of WMO, a climatic study of warming/cooling of the atmospheric column by solar and terrestrial radiations over India in different seasons has been undertaken. In this paper the absorption in the atmosphere of direct short-wave radiation from the sun and diffuse short-wave radiation from the earth in the month of January (over India) is presented. It shows that only about 25 percent of the incident direct solar radiation, viz., solar constant (Approx. 1360 W/ m2), is absorbed in the atmosphere (345 W/m2) and up to 500mb absorption is just about 1 percent of the amount at the top of the atmosphere. Between 500 and 850mb the absorption is about 26 per cent of it, but between 850mb and the surface it is 34 per cent. Thus, the lowest - half of the atmosphere (below 500mb) absorbs almost 60 per cent of the absorbed part of total short-wave radiation in the atmosphere and of this the major portion is absorbed in the lowest 1500 metres.